Coronary imaging of cardiac allograft vasculopathy predicts current and future deterioration of left ventricular function in patients with orthotopic heart transplantation. Issue 2 (9th November 2021) - Reddy, S Ashwin; Khialani, Bharat V; Lambert, Ben; Floré, Vintcent; Brown, Adam J; Pettit, Steve J; West, Nick EJ; Lewis, Clive; Parameshwar, Jayan; Bhagra, Sai; Kydd, Anna; Hoole, Stephen P
Abstract: Background: Intravascular ultrasound (IVUS) and optical coherence tomography (OCT) improve sensitivity of cardiac allograft vasculopathy (CAV) detection compared to invasive coronary angiography (ICA), but their ability to predict clinical events is unknown. We determined whether severe CAV detected with ICA, IVUS, or OCT correlates with graft function. Methods: Comparison of specific vessel parameters between IVUS and OCT on 20 patients attending for angiography 12–24 months post‐orthotopic heart transplant. Serial left ventricular ejection fraction (EF) was recorded prospectively. Results: Analyzing 55 coronary arteries, OCT and IVUS correlated well for vessel CAV characteristics. A mean intimal thickness (MIT)OCT > .25 mm had a sensitivity of 86.7% and specificity of 74.3% at detecting Stanford grade 4 CAV. Those with angiographically evident CAV had significant reduction in graft EF over 7.3 years follow‐up (median ΔEF ‐2% vs +1.5%, P = .03). Patients with MITOCT > .25 mm in at least one vessel had a lower median EF at time of surveillance (57% vs 62%, P = .014). Two MACEs were noted. Conclusion: Imaging with OCT correlates well with IVUS for CAV detection. Combined angiography and OCT to screen for CAV within 12–24 months of transplant predicts concurrent and future deterioration in graft function.